Nosocomial Infection in MICU: An Observational Study - Chennakesavulu Dara; Surendra Babu Darivemula; Triven Sagar Sandepogu; M. Saranya; N. Vijayalakshmi; S. Swetha (Wolters Kluwer Medknow Publications, 2023)
Introduction: Nosocomial infections are infections; patients acquire while admitted to a health-care facility and generally develop 48 h or later after admission. These infections can lead to serious problems such as sepsis and even death. Materials and Methods: A prospective observational study was conducted for 6 months to estimate the incidence of nosocomial infections acquired in the medical intensive care unit (MICU), their risk factors, the causative pathogens, and the outcome. The patients admitted for more than 48 h to the MICU and willing to give consent were included in the study. Of 496 patients in MICU, 216 patients stayed 48 h and Acute Physiology and Chronic Health Evaluation II (APACHE II) score during the first 24 h of admission to the MICU. Results: The incidence of nosocomial infections in MICU was 14.9% (32 out of 216). Age, APACHE II score >13, MICU stay >7 days, and comorbidities such as peripheral venous line, central venous catheter, duration of urinary catheterization, duration of endotracheal intubation, nasogastric tube, and mechanical ventilator of >7 days were found to be independent risk factors of acquiring nosocomial infections (P < 0.05). Important causative organisms for nosocomial infections were Pseudomonas aeruginosa in 18 patients (32.72%), Escherichia coli in 11 (20.0%), Acinetobacter species in 8 (14.54%), and Klebsiella pneumoniae in seven patients (12.72%). Mortality among patients with nosocomial infections was 25% (8/32) and among those without nosocomial infections was 6.5% (12/184), P = 0.002. The length of ICU stay was higher in patients with nosocomial infections (15.42 ± 6.93 days) than in those without nosocomial infections (6.7 ± 5.14 days), P < 0.001. Conclusion: Nosocomial infections are common in ICU settings and contribute to significant mortality and morbidity. Infection control strategies are necessary to reduce nosocomial infection rates as well as ICU mortality and morbidity.